Our Experience in the Correction of Acetabular Dysplasia Using the Proposed Modification of Pelvic Osteotomy - Suvorov, V.L.; Filipchuk, V.V.; Melnyk, M.V. (TERRA ORTHOPAEDICA, 2025)
Introduction. The proper application of pelvic osteotomies for the surgical treatment of developmental dysplasia of the hip (DDH) plays a key role in correcting acetabular dysplasia and preventing secondary hip osteoarthritis. For the correct application of pelvic osteotomies, it is mandatory to understand the three-dimensional morphology of the acetabulum and accurately determine the direction of acetabular dysplasia correction. Currently, there is no described pelvic osteotomy, which can improve femoral head coverage in any direction without significant technical limitations.Objective. This study aims to evaluate the outcomes of the modified Salter pelvic osteotomy performed at the Department of Reconstructive Orthopedics and Traumatology for Children and Adolescents at the SI “Institute of Traumatology and Orthopedics of NAMS of Ukraine.”Materials and Methods. 21 patients with DDH aged 2-6 years were selected for the retrospective study; 3-D acetabular morphology was assessed with further application of the proposed modified Salter osteotomy for correcting acetabular dysplasia.Results. A methodology for assessing the 3-D morphology of the acetabulum and determining the correction vectors for acetabular dysplasia was developed and implemented; the mid-term postoperative results after applying the proposed modification of Salter pelvic osteotomy were evaluated. The modification demonstrated significant improvement in acetabular parameters: preoperative acetabular index (AI) was 46.8 ± 12°, postoperative AI was 24.3 ± 5.1°, with a mean correction of 23.1 ± 4.9°. Further positive dynamics were observed: AI at 6 months postoperatively was 19.8 ± 4.7°, and at the final follow-up examination, it reached 15.6 ± 4.4°, while Wiberg’s angle improved to 23.3 ± 3.9°. Excellent and good clinical outcomes were observed in 57.2% and 33.3% of cases, respectively, with radiological outcomes showing excellent and good results in 66.7% and 23.8% of cases. A relatively high rate of femoral head avascular necrosis (AVN) (33.3%) correlated with a high percentage of patients with complete hip dislocation (61.9%). However, most patients with AVN (23.8%) subsequently experienced near-complete or complete restoration of femoral head structure and shape.Conclusions. 3-D acetabular morphology assessment is a key factor for the successful surgical correction of residual acetabular dysplasia in DDH cases. The proposed modification of the Salter pelvic osteotomy provides excellent and good mid-term clinical and radiological outcomes in most cases.